ANALYSIS OF CONTAMINATION OF SOME REGIONS WITH HEAVY METALS IN WATER BODIES AND SOIL (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
The article describes the influence of heavy metals in water and soil on the reduction of yields in the cultivation and production of agricultural products and methods of combating it.